SOLUTION: Solve: 1 + 4(2c- 3) = 3(3c-5)
-> SOLUTION: Solve: 1 + 4(2c- 3) = 3(3c-5)
solves your algebra problems and provides step-by-step explanations!
: algebra software solves algebra homework problems with step-by-step help!
Algebra: Expressions involving variables, substitution
If you need
immediate math help from PAID TUTORS right now
, click here
. (paid link)
Click here to see ALL problems on Expressions-with-variables
Solve: 1 + 4(2c- 3) = 3(3c-5)
put this solution on YOUR website!
1 + 4(2c- 3) = 3(3c-5)